Understanding Subject Knowledge for Primary Teaching - Pope, Deborah; Pope, Deborah (SAGE Publications, 2019)
How can trainee teachers begin their careers with a clear understanding of all the curriculum subjects? This book addresses the nature of subject knowledge in all foundation curriculum subjects. It deconstructs the elements of each subject through an exploration of the nature of the subject, a coverage of the 'skills' a study of this subject develops and through detailed analysis of case studies from practice. At a time when concerns about the lack of breadth in the primary curriculum are being voiced, this book supports busy trainee teachers to truly understand and be ready to teach all curriculum areas.